Developmental patterns of postictal refractoriness and potentiation akin to cortical stimulation - Mareš, Pavel; Kubová, Hana (Epilepsia, 2015)
Postictal refractoriness checked by paired stimulations of the limbic structures was demonstrated to fail in rats<2 weeks old. Cortical epileptic afterdischarges were used in our study to examine if this phenomenon is restricted to old cortical structures or if it is a general one. Rats 12, 15, 18, 25, and 90 days old with implanted electrodes formed the experimental groups. Stimulation was performed by 15-s series of 1-msec pulses with suprathreshold intensity and frequency of 8 Hz. Paired stimulation of the cerebral cortex in 12-day-old rats elicited the second afterdischarge, even if the 30-s interval was used. Refractoriness started to appear in the third postnatal week and developed progressively so that 25-day-old rats did not differ from adult animals, that is, an interval longer than 1 min was necessary for elicitation of the second seizure.
Keywords: záchvaty; Animals, Newborn; Electroencephalography; elektrická stimulace; elektroencefalografie; mozková kůra; Electric Stimulation; Seizures; refrakterní doba elektrofyziologická; novorozená zvířata; Limbic System; implantované elektrody; krysa rodu Rattus; limbický systém; Animals; Electrodes, Implanted; zvířata; Rats; Refractory Period, Electrophysiological; Cerebral Cortex